Intravitreal administration of recombinant human opticin protects against hyperoxia-induced pre-retinal neovascularization. (February 2022) - Klaska, Izabela P.; White, Anne; Villacampa, Pilar; Hoke, Justin; Abelleira-Hervas, Laura; Maswood, Ryea N.; Ali, Robin R.; Bunce, Catey; Unwin, Richard D.; Cooper, Garth J.S.; Bishop, Paul N.; Bainbridge, James W.
Abstract: Opticin is an extracellular glycoprotein present in the vitreous. Its antiangiogenic properties offer the potential for therapeutic intervention in conditions such as proliferative diabetic retinopathy and retinopathy of prematurity. Here, we investigated the hypothesis that intravitreal administration of recombinant human opticin can safely protect against the development of pathological angiogenesis and promote its regression. We generated and purified recombinant human opticin and investigated its impact on the development and regression of pathological retinal neovascularization following intravitreal administration in murine oxygen-induced retinopathy. We also investigated its effect on normal retinal vascular development and function, following intravitreal injection in neonatal mice, by histological examination and electroretinography. In oxygen-induced retinopathy, intravitreal administration of human recombinant opticin protected against the development of retinal neovascularization to similar extent as aflibercept, which targets VEGF. Opticin also accelerated regression of established retinal neovascularization, though the effect at 18 h was less than that of aflibercept. Intravitreal administration of human recombinant opticin in neonatal mice caused no detectable perturbation of subsequent retinal vascular development or function. In summary we found that intraocular administration of recombinant human opticin protects against the development of pathological angiogenesis in mice and promotes its regression. Highlights: Human recombinant opticin protects against the development of pathological angiogenesis in mice. Human recombinant opticin accelerates regression of established pre-retinal neovascularization in mice. Intraocular administration of recombinant human opticin offers the potential for a safe and effective therapy for neovascular retinal diseases.